1969
DOI: 10.1021/i260029a017
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocracking of Gas Oil

Abstract: Gas oil boiling in the range 300°to 430°C. was hydrocracked in a conventional continuous fixed-bed tubular flow reactor over a dual-functional catalyst. Gasoline of almost the same composition was produced in yields of 60, 82, and 58% in the single-pass, double-pass, and recycle operations, respectively, with diesel oil of 50 diesel index as a by-product. Hydrocracking of gas oil proceeds through a mechanism involving a combination of simultaneous and consecutive bond-breaking reactions followed by isomerizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(40 citation statements)
references
References 5 publications
4
35
1
Order By: Relevance
“…The precise reason that ALA yields more H 2 than ALA-Mt (Na) is still unclear to us. The produced H 2 was likely involved in the hydrogenation reaction; this is supported by several previous studies (Mango, 1996;Qader and Hill, 1969) in which H 2 was found to react with some intermediate organics during hydrocarbon cracking and to be active in hydrogenation.…”
Section: Effects Of Mt On the Isomerization Alkene-alkane Conversionsupporting
confidence: 78%
“…The precise reason that ALA yields more H 2 than ALA-Mt (Na) is still unclear to us. The produced H 2 was likely involved in the hydrogenation reaction; this is supported by several previous studies (Mango, 1996;Qader and Hill, 1969) in which H 2 was found to react with some intermediate organics during hydrocarbon cracking and to be active in hydrogenation.…”
Section: Effects Of Mt On the Isomerization Alkene-alkane Conversionsupporting
confidence: 78%
“…(8), activation energy E and frequency factor A are taken as 88.28 kJ·mol -1 and 1.0×10 7 (volume of feed)·(volume of catalyst) -1 ·h -1 (Qader and Hill, 1969). ρ HVGO and ρ catalyst are the density of HVGO and catalyst.…”
Section: Reaction Modelingmentioning
confidence: 99%
“…We only extract a small number of complete data sets from 4 months of plant data by considering the following: (1) each product stream has its own analysis period, and the analyses of all product streams performed on the same day is not available; (2) it is necessary to find out the date that includes most analysis data and fill up the missing data from adjacent days; (3) some of the meters fail to record correct values during the period; and (4) some of the data sets fail in mass balance checking (see section 4.3 for the procedure of mass balance calculation). Therefore, it is always useful to collect a long period (1À3 months) of data for modeling purposes, particularly for a commercial process.…”
Section: Energy and Fuelsmentioning
confidence: 99%
“…Although the procedure of building a reactor model depends upon the selection of the kinetic model, we require the following tasks in developing a model for most commercial HCR processes: (1) do the feedstock analysis based on the selected kinetic model; (2) represent the feedstock as a mixture of kinetic lumps, which can be modeling compounds or pseudo-components based on boiling point ranges; (3) build the reaction network, define rate equations, and estimate rate constants and heat of reaction; (4) apply the feed oil (density, distillation curve, total sulfur, total nitrogen, and basic nitrogen) all gas products, including purge gas (composition analysis) composition analysis of light naphtha all liquid products from the fractionator (density, distillation, element analysis of C, H, S, and N) composition analysis of sour water composition analysis of lean amine and rich amine makeup H 2 (composition analysis) recycle H 2 (composition analysis) purge gas (composition analysis) low-pressure separator gas (composition analysis) others bed temperature at the start of run (SOR) provided by the catalyst vendor bed temperature at the end of run ( We describe in section 2 the concept of the backward approach in representing the feedstock using the Aspen HYSYS/Refining. Because the refinery does not routinely do a comprehensive analysis of HCR feedstock, this work applies the backward approach to characterize the feedstock.…”
Section: Reactor Model Developmentmentioning
confidence: 99%